ESTIMATES OF ENERGY AND PROTEIN FRACTIONS OF CROP RESIDUE BASED COMPLETE RATIONS - K. Raja Kishore; D. Srinivas Kumar; J.V. Ramana; A. Ravi; E. Raghava Rao (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A study was undertaken to evaluate carbohydrate and protein fractions of crop residue based complete rations as per the procedure of Cornel Net Carbohydrate and Protein (CNCPs) system. Three iso-nitrogenous complete rations were prepared comprising of maize stover (T1) straw , red gram straw (T2) and black gram (T3) and concentrate mixture in 60: 40 ratio, respectively and were analyzed for CNCPS fractions. Maize stover contained lower (P<0.01) lignin (% NDF) compared to red gram or black gram straws. Lignin (% NDF) was lower (P<0.01) and starch (% NSC) was higher (P<0.01) in T1 when compared to T2 or T3. NDICP (% CP) was higher (P<0.01) and ADICP (% CP) was lower (P<0.01) in T1 when compared to other complete rations. Carbohydrate fraction CA (% CHO) was higher (P<0.01), while fraction CC (% CHO) was lower (P<0.01) in T1 when compared to other complete rations. Protein fractions PB1 and PB3 (% CP) were higher (P<0.01) in T1 while the fraction PC (% CP) was similar among the complete rations under study. Similar trend of higher (P<0.01) CA, PB2 and PB3 and lower (P<0.01) CC fractions were observed in maize stover than in red gram or black gram straw. The present study concluded that complete ration (T) comprising of maize stover was better in terms of carbohydrate and protein fractions with higher (CA, PB1and PB3) and lower CC and PC fractions when compared to other complete rations.